2020
DOI: 10.1186/s12883-020-01685-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-radiological dissociation in a patient with nitrous oxide-induced subacute combined degeneration: a case report

Abstract: Background: Several recent studies have reported subacute combined degeneration (SCD) induced by nitrous oxide (N 2 O) abuse. However, the association between the evolution of dynamic neuroimaging and clinical manifestations has not been reported in patients with N 2 O-induced SCD. Case presentation: We described the case of a 24-year-old man who developed SCD with inverted V-sign hyperintensities over the posterior aspect of the spinal cord caused by frequent, excessive N 2 O inhalation. One month after treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In our study, 53% of the patients showed abnormal signals in the cervical spinal cord, mostly associated with only the posterior funiculus, which is in agreement with previous findings about SCD (Cao et al, 2018). A previous study had shown that the evolution of conventional MRI findings lagged compared to the clinical manifestation because T2-weighted imaging is not sensitive enough to show cytotoxic edema, suggesting clinical-radiological dissociation (Jiang & Shang, 2020); moreover, we also found that the incidence of MRI lesions is higher in patients with an N 2 O exposure time of ≤6 months. Peripheral nerve damage is common in N 2 O abusers.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 53% of the patients showed abnormal signals in the cervical spinal cord, mostly associated with only the posterior funiculus, which is in agreement with previous findings about SCD (Cao et al, 2018). A previous study had shown that the evolution of conventional MRI findings lagged compared to the clinical manifestation because T2-weighted imaging is not sensitive enough to show cytotoxic edema, suggesting clinical-radiological dissociation (Jiang & Shang, 2020); moreover, we also found that the incidence of MRI lesions is higher in patients with an N 2 O exposure time of ≤6 months. Peripheral nerve damage is common in N 2 O abusers.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, N 2 O has gained increasing popularity worldwide especially among young people due to its euphoric effects [ 10 , 11 ]. According to previous studies, it is not unusual that N 2 O can cause cobalamin deficiency and SCD [ 5 , 7 , 11 13 ]. Although serum vitamin B 12 is a most convenient and accessible laboratory approach to evaluate cobalamin deficiency, it is to note that quite a few SCD patients are detected with normal or elevated serum vitamin B 12 [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated the possible reasons are as follows: Copper is a cofactor for a variety of biological reactions and thought to be necessary for methionine synthase and S-adenosylhomocysteine hydrolase, which play vital roles within the methylation cycle [ 10 ]. N 2 O can oxidize the cobalt ion which attenuates the function of methylcobalamin, inhibits methionine synthase, and elevates the concentration of homocysteine [ 5 ]. This might be followed by a decrease in the activity of S-adenosylhomocysteine hydrolase and a consequent decline in copper concentration by feedback regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B12 supplementation should be started immediately upon suspected diagnosis since the response to treatment is associated with the severity and duration of symptoms. The recovery time will depend on the severity of symptoms and the degree of lesions in the spinal cord [ 7 ]. Patients should be educated on the importance of the cessation of the recreational use of nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%